Density of mangrove trees in selcted municipalities in the province of Antique, Panay Island, Philippines. - Arelis, Ian Jerwin Conanan
This study focuses only in determining the density of mangrove trees occuring in selected municipalities in the Province of Antique, Panay Island, Phils. by species identification, ocular survey and transect-line plot method.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Mangroves trees